Comparison of the predictive value of plateletcrit with various other blood parameters in gestational diabetes development. (3rd July 2016) - Sahbaz, Ahmet; Cicekler, Humeyra; Aynioglu, Oner; Isik, Hatice; Ozmen, Ulku
Abstract : Gestational diabetes is the most encountered metabolic disease in pregnancy and affects both the mother and fetus adversely. Low-grade subchronic inflammation is associated with gestational diabetes development. Platelets (PLT) play role in blood coagulation and inflammatory process. We aimed to compare the various platelet indices in patients with GDM and healthy pregnant controls and to determine whether PLT indices are useful in Gestational diabetes diagnosis. The present study was performed at the Zonguldak Bulent Ecevit University, School of Medicine, Department of Obstetrics and Gynecology. Statistically significant relationships with plateletcrit, mean platelet volume, and platelet distribution width and patients with GDM were found ( p  < 0.001). Plateletcrit had higher sensitivity and specificity than other platelet indices. Although plateletcrit is a largely unknown or an underestimated parameter in complete blood count, it gives more precise information than platelet count and mean platelet volume. Platelet-related indices and their determination are inexpensive and routinely ordered markers, the significance of which is often ignored. They may be useful in screening for gestational diabetes as an adjunct to oral glucose tolerance test.